Analisis Inovasi Pendidikan Dalam Konteks Organisasi Sosial Keagamaan: Studi Muhammadiyah dan NU - Mulia Sakti; Hadi Syaputra Panggabean (At Turots: Jurnal Pendidikan Islam, 2024)
In recent years, global transformations and technological advancements have significantly impacted the education sector. Therefore, it is important to examine the extent to which Islam, whether in the Muhammadiyah or NU context, has adapted to these changes through educational innovation. The aim of this research is to understand educational innovation in the context of religious social organizations: a study of Islamic religion. The research method employed in this study is the literature review method. The results of this research indicate that educational innovation is a necessity that arises in response to the dynamics of development in various aspects of life. This involves a vision for education, adaptation to population growth, integration of scientific developments into the curriculum, and meeting the demands for an education process relevant to the needs of society and the workforce. Educational innovation must be intelligent in accommodating technological, behavioral, organizational, and social changes to provide quality education in line with the demands of the times